2015
DOI: 10.18575/msrs.sm.e.15.04
|View full text |Cite
|
Sign up to set email alerts
|

Personal Characteristics and Burnout Syndrome among Teachers of Primary and Secondary Schools

Abstract: Introduction: Burnout syndrome is more often seen in human (assisting) services professions which provide services to population. An interaction between external and internal factors has great importance in burnout syndrome occurrence. According to previous research, personal characteristics, especially neuroticism and extraversion, have a significant role in the development of burnout syndrome. The aim of study: This research will establish whether the personal characteristics and demographic variables have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
1
6
2
Order By: Relevance
“…In the Federation of BiH, predominant populations are Bosnian (Muslim) and Croatian (Catholic), while in the Republic of Srpska the population is mostly Serbian (Orthodox). Until now, only a small study in school teachers has been performed in the Republic of Srpska indicating a low percentage of burnout syndrome in this population and contradicting previously published studies as well as indicators of increased stress in this population due to the conflicts, political, national, and religious tensions [19].…”
Section: Introductioncontrasting
confidence: 66%
“…In the Federation of BiH, predominant populations are Bosnian (Muslim) and Croatian (Catholic), while in the Republic of Srpska the population is mostly Serbian (Orthodox). Until now, only a small study in school teachers has been performed in the Republic of Srpska indicating a low percentage of burnout syndrome in this population and contradicting previously published studies as well as indicators of increased stress in this population due to the conflicts, political, national, and religious tensions [19].…”
Section: Introductioncontrasting
confidence: 66%
“…However, other studies found that male teachers suffer from burnout more than females in one or more burnout dimensions (Al-Ayasrah & Abdel Rahman, 2013;Al-Farah, 2001;Gumaiha, 2012;Maslach & Jackson, 1981). In contrast, several studies found no significant differences between female and male teachers within the three burnout dimensions (Bakhit & Hassan, 2011;Dbaby, 2012;El-Omari & Freihat, 2011;Ozan, 2009;Paleksic et al, 2015). egarding the nationality, very few studies explore the effect of teachers' nationality, whether local or foreigner, on their burnout levels.…”
Section: Studies On Teachers' Burnoutmentioning
confidence: 97%
“…Primary school teachers in North Dakota in the United States (Mowers, 2010) and Turkey (Ozan, 2009) reported moderate levels of emotional burnout. However, primary school teachers reported lower levels of burnout in countries such as, Sweden (Arvidsson et al, 201 ), Serbia ( an elovic & Sto il kovic , 2015), the Republic of Srpska (Paleksic et al 2015), Turkey (Yerdelen et al, 2016), Iraq (Soleman & Edrees, 2007) and Sudan (Gumaiha, 2012).…”
Section: Studies On Teachers' Burnoutmentioning
confidence: 99%
See 2 more Smart Citations